MENINGKATKAN HASIL BELAJAR BULUTANGKIS PENDEKATAN LONTON PENJASORKES SISWA KELAS V (Department of Physical Education, Sport, Health and Recreation, 2013)
Outcomes of learning badminton at SDN Baros 01 is still less than the KKM. Percentage of49.09% indicates mastery. The problem in this study is whether there is an increase in learningoutcomes in badminton with Lonton approach Penjasorkes in class V SDN Baros 01 SubKetanggunganBrebes? The purpose of this study to determine improved learning outcomesbadminton badminton after getting learning approach Lonton game. The method of researchis a class act consisting of two cycles. The results of this study indicate that the learning gameof badminton with Lonton approach step by step to achieve success. With the following data:first cycle to obtain an average value of 74.1% and the second cycle with an average value of84.9%. As for the value of student learning outcomes in the first cycle is only 60% the numberof students who have not completed 22 children and the second cycle reaches 100%, whichmeans that every child has reached the KKM set. Improve learning outcomes approach to thegame of badminton with Lonton in Penjasorkes in class V SDN Baros 01 Sub KetanggunganBrebesshow success. Penjasorkes advice to teachers to use the material Lonton badmintongame, the students can be used as badminton practice for schools to provide learning infrastructure,Lonton game can be used as an alternative in learning badminton.